BIOACTIVITY OF EPIDERMAl SECRETION OF TWO MARINE CATFISH FROM MUMBAI - Deo, A. D.; Venkateshvaran, K.; Devaraj, M. (Journal of Indian Fisheries Association, 2008)
Crude mucus and its partially purified fractions from two marine catfish from Mumbai, Arius dussumieri and Osteogeneiosus militaris were assayed for their crinotoxicity through assays for hemolysis and haemagglutination of chicken erythrocytes, formation of paw edema in mice, and antibacterial activity against one gram-positive and four gram-negative bacteria. Assays were also done to block the edema using Phineramine maleate, Piroxicam, and Atropine sulfate. Crude toxin as well as their fractions from both the fishes exhibited haemolytic and haemagglutinating activities on chicken blood, besides edematous activity in mice models. The edematous activity was blocked by Phineramine maleate and Piroxicam but enhanced by Atropine sulfate; however, all these activities, either blocking or enhancing, were statistically insignificant. Antibacterial activity was absent in all the extracts tested. Keywords: marine catfish, crinotoxicity, haemolysis, haemagglutination, edema, antidote.